EP 67. Effects of cTBS over the posterior parietal cortex on body sway and the integration of light tactile fingertip contact. Issue 9 (September 2016) - Kaulmann, D.; Johannsen, L.
Abstract : Introduction: Light contact with an earth-fixed referent reduces body sway in quite standing.Johannsen et al. (Neuroscience Letters, 2014) investigated the progression of sway before and after the passive onset and removal of right-hand fingertip contact. They found that rTMS over the left inferior parietal gyrus (IPG) reduces overshoot of sway after contact removal, which indicates that left IPG plays a role in sensory reorganisation for sway control with right-handed fingertip contact.Bolton et al. (Neuroreport, 2012) demonstrated that disrupting the right prefrontal cortex altered the processing of right arm sensory information in the context of standing balance with light touch. With respect to the hemispheric processing of tactile information in an egocentric frame of reference, Azañón et al. (Current Biology, 2010) showed that disruption of the right posterior parietal cortex (rPPC) impaired position judgements of tactile stimuli on the left forearm relative to the face. These results might indicate that the right hemisphere is involved in the processing of touch within spatial reference frames for postural control of both hands, while the left hemisphere evaluates contralateral touch only. In the present study we aimed to investigate the effects of continuous theta burst stimulation (cTBS) over the right and left (PPC) on body sway and the integration of light tactile fingertip contact. Methods: In 14 right-handed young adults, cTBS of an intensity of 80% of the passive motor threshold was applied for 60 seconds over the left and right PPC. In addition, a sham condition was included either over the left or right PPC. Target locations were identified using real-time neuronavigation software. Participants were tested blindfolded in quiet upright Tandem-Romberg stance before and after each stimulation interval. They were instructed to actively initiate and cease finger contact with an earth-fixed referent in response to an acoustic signal. Testing was carried out on two non-consecutive sessions. Body sway was evaluated in terms of Centre of Pressure (CoP) and trunk kinematics in addition to forces and torques at the contact point. Results: Current results reveal that cTBS over the right PPC affected postural control in general. The overall level of body sway was decreased irrespective of the availability of fingertip contact. This general effect was not found for either the left PPC or the sham conditions. Conclusion: Generally reduced sway may be a sign of a postural control strategy that involves a greater number of co-contractions, which does not automatically imply an improved postural stability. Another possible explanation is that inhibition of the right PPC limits processes involved in the active exploration of the body's stability state (Ehrenfried et al. ).